Sensor a fibra ótica encapsulado em resina polimérica com reforço de fibra de vidro para aplicação em gerador de alta potência - Galvão, José Rodolfo (2015)
This work presents an application of optical fiber sensors based on Bragg gratings encapsulated in polymeric composite resin with glass fiber reinforcement. Three commercial epoxy resins were evaluated. The main objective of the study is to characterize the composites and investigate the feasibility of embedding the optical fiber sensors based on Bragg gratings in epoxy composite. In the characterization of the samples tensile tests were performed to evaluate the residual stress after the curing process. The residual stress was investigated by mains of a FBG sensor embedded in the composite. Additionally, tests were conducted to evaluate the glass transition temperature by DSC technique. The values of the axial tensile and simple flexural stress were investigated using a universal testing machine. In addition, tests were performed for evaluating the composite behavior when subjected to a fixed load and variable temperature ranging from 20 °C to the temperature limit of the glass transition of the composite. The results show a high level of integration of the FBGs with the epoxy composite. One of the results is promising for applications in a high power generator and in hostile environments working at temperatures up to 127 °C.